2003
DOI: 10.1080/10284150310001624183
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Evoked Response in Juvenile Rats Fed Rat Milk Formulas with High Docosahexaenoic Acid

Abstract: In contrast to the longer ABR in juvenile offspring of rats fed high-DHA through gestation and lactation, ABR was shorter in juvenile rats fed high-DHA diets only after birth than rats fed ARA + DHA. Further studies are needed to understand the relationship between dietary DHA, norepinephrine, and auditory system development over a range of DHA intakes and discrete periods of development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Maturation and increasing specificity of auditory sensory systems, fundamental to developmental sensitivities of grammatical and semantic/lexical (object-word association) language learning, involve a gradual decrease in responses of occipital regions to auditory stimuli from 6 to 36 mo of age. Although apparently not studied in humans, experimental work has reported evidence of altered auditory evoked potentials in offspring of animals given DHA during pregnancy [56]. We found no evidence of fetal DHA insufficiency sufficient to constrain cognitive, gross motor or fine motor development when assessed using the BSID-III at 18 mo of age.…”
Section: Discussioncontrasting
confidence: 59%
“…Maturation and increasing specificity of auditory sensory systems, fundamental to developmental sensitivities of grammatical and semantic/lexical (object-word association) language learning, involve a gradual decrease in responses of occipital regions to auditory stimuli from 6 to 36 mo of age. Although apparently not studied in humans, experimental work has reported evidence of altered auditory evoked potentials in offspring of animals given DHA during pregnancy [56]. We found no evidence of fetal DHA insufficiency sufficient to constrain cognitive, gross motor or fine motor development when assessed using the BSID-III at 18 mo of age.…”
Section: Discussioncontrasting
confidence: 59%
“…The differences in the distribution at P10 and P14 in OSB indicated that the mature synaptic connections were established between OHCs and nerve terminals; this phase was also consistent with the onset of hearing. 2 The distribution differences between groups showed that the OHCs were controlled by the SGNs, which released neurotransmitters, but the concrete mechanism requires further investigation. Similarly, changes in hair cell function during neurite retraction and synapse pruning may also contribute to variation in synaptic stability.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the rat auditory system lasts from the embryonic period to 14 days after birth. 1,2 . The maturation of the auditory system has been shown to be affected by the external environment, hormones and other factors after birth.…”
Section: Introductionmentioning
confidence: 99%
“…Postnatal formula supplementation with DHA + AA resulted in longer latencies compared to supplementation with DHA alone or to the control group (Auestad et al, 2003). However the application of experimental animal studies to human nutrition ones is limited by differences in auditory development and doses provided.…”
Section: Resultsmentioning
confidence: 96%